Generalized arterial calcification of infancy with a novel ENPP1 mutation: a case report - Iole Brunod; Barthélémy Tosello; Sophie Hassid; Catherine Gire; Laurent Thomachot; Michel Panuel (BMC, 2018)
Abstract Background Generalized Arterial Calcification of Infancy (GACI) is a heritable ectopic mineralization disorder resulting in diffuse arterial calcifications and/or stenosis, mostly caused by mutations in the ENPP1 gene. Here we present a case report of GACI in a male infant with a new familial mutation of the ENPP1 gene and the clinical outcome after biphosphonates therapy. Case presentation The clinical presentation was characterized by a severe early-onset of hypertension refractory to multiple therapy. To investigate this atypical hypertension, a renal Doppler ultra-sonography was performed and diffuse echo-bright arteries were detected; then a low-dose whole-body computed tomography demonstrated extensive arterial calcifications, suggesting GACI. A novel homozygous mutation c.784A > G (p.Ser262Gly) was detected in the ENPP1 gene. The infant was administered four courses of bisphosphonates: arterial calcifications were found to decrease but severe refractory hypertension was persistent. Although GACI can be a rapidly fatal illness and frequently results in death in infancy, the patient was 24 months of age at the time of writing this report. Conclusions Three points of interest: the first one is to remind clinicians of this rare and atypical etiology in neonates with severe hypertension and in fetuses with cardiomyopathy and non-immune hydrops fetalis. The second point is the identification of a novel mutation in the ENPP1 gene associated with a clinical presentation of GACI. The third point is the fairly favourable outcome of our patient after bisphosphonates therapy, with calcifications regression but not hypertension.